2021
DOI: 10.3390/cells10081907
|View full text |Cite
|
Sign up to set email alerts
|

Role of Neuroglobin in the Neuroprotective Actions of Estradiol and Estrogenic Compounds

Abstract: Estradiol exerts neuroprotective actions that are mediated by the regulation of a variety of signaling pathways and homeostatic molecules. Among these is neuroglobin, which is upregulated by estradiol and translocated to the mitochondria to sustain neuronal and glial cell adaptation to injury. In this paper, we will discuss the role of neuroglobin in the neuroprotective mechanisms elicited by estradiol acting on neurons, astrocytes and microglia. We will also consider the role of neuroglobin in the neuroprotec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 102 publications
(151 reference statements)
0
11
0
Order By: Relevance
“…17β-Estradiol (E2), an isomer of estradiol that is the most potent estrogen, is able to induce upregulation of the expression of neuroprotectant neuroglobin (NGB) to counteract H 2 O 2induced apoptosis (De Marinis et al, 2013;Barreto et al, 2021). Exposure to 17β-estradiol also protects the brain against reperfusion injury after acute ischemic insults by reducing lesion formation and brain atrophy, as well as improving cerebral blood flow in rat ischemic stroke (Carpenter et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17β-Estradiol (E2), an isomer of estradiol that is the most potent estrogen, is able to induce upregulation of the expression of neuroprotectant neuroglobin (NGB) to counteract H 2 O 2induced apoptosis (De Marinis et al, 2013;Barreto et al, 2021). Exposure to 17β-estradiol also protects the brain against reperfusion injury after acute ischemic insults by reducing lesion formation and brain atrophy, as well as improving cerebral blood flow in rat ischemic stroke (Carpenter et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Modulation of the hippocampal function by estrogens contributes to the estrogenic facilitation of learning and memory through diverse aspects, such as intracellular cascade, dendritic spinogenesis, and synaptic function and plasticity, and it protects hippocampal cells against excitotoxicity arising from drugs ( Taxier et al, 2020 ). 17β-Estradiol (E2), an isomer of estradiol that is the most potent estrogen, is able to induce upregulation of the expression of neuroprotectant neuroglobin (NGB) to counteract H 2 O 2 -induced apoptosis ( De Marinis et al, 2013 ; Barreto et al, 2021 ). Exposure to 17β-estradiol also protects the brain against reperfusion injury after acute ischemic insults by reducing lesion formation and brain atrophy, as well as improving cerebral blood flow in rat ischemic stroke ( Carpenter et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, menopause also increases the risk of Parkinson’s disease in women [ 4 ], even though there are 50% more males with Parkinson’s than females. Given the neurodegenerative nature of these diseases, it is believed that this relationship may be associated with the neuroprotective effects of oestrogens [ 5 , 6 , 7 ]. However, little is known about reprogrammed responses to hormone replacement therapies following hormonal deprivation, and if such reprogramming is preventable or rescuable.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence has clearly demonstrated that the oxygen-binding protein Ngb [ 12 ] is an endogenous neuroprotective molecule in numerous neurological diseases, and particularly against hypoxic/ischemic (H/I) and oxidative stress-related insults [ 13 ]. Its neuroprotective activity has been described in numerous publications from cultured neurons to animal models [ 14 , 15 , 16 , 17 , 18 , 19 ], although the molecular mechanisms on which Ngb bases its neuroprotective ability are just beginning to be investigated [ 20 ]. Specifically, it is known that Ngb interacts with proteins involved in signal transduction and regulation, such as PI3K or AMP-activated protein kinase (AMPK), both involved in mitochondrial functions and cell metabolism [ 21 ].…”
Section: Introductionmentioning
confidence: 99%